STRATEGI PEMASARAN PRODUK MULIA PADA PEGADAIAN SYARIAH HASANUDDIN KABUPATEN GOWA - Arfah, Muhammad; Syafrimansyah, Syafrimansyah (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
The research aims to determine the Marketing Strategy of Mulia Product at Pegadaian Syariah Hasanuddin and to find out the development of mulia product used by Pegadaian Syariah Hasanuddin in marketing mulia product. The type of research used is a qualitative approach with data collection techniques in the form of interview guidelines and documentation to describe the results of observing reality and developing a theory of marketing strategies for Pegadaian Syariah Hasanuddin mulia product and the obstacles it faces. From the results of the study, it can be concluded that the strategy used is literacy of the community and offers investment by way of gathering precious metals, promoting mulia product and providing discounts for advances and holding gold bazaar activities with payment transactions in cash or installments. The obstacles they face are that people’s harvest fail, some areas of the community lack knowledge about noble products and people are more interested in gold jewelry than gold bullion.